Laughter as ideological symptom: dialogical analysis of older adults’ discourse - Haye, Andrés; Torres-Sahli, Manuel (Frontiers in Psychology, 2025)
IntroductionLaughter is increasingly investigated in ageing discourse, yet its ideological functions remain unclear. This paper examines how laughter functions as an ideological symptom in the discourse of older adults regarding aging. Drawing from Voloshinov’s dialogical theory, we conceptualize laughter not merely as an emotional response, but as an ideological symptom revealing tensions between what is said and what remains assumed.MethodsFour focus-group interviews with Chilean participants (n = 20; age 60–86) were analysed with a three-phase qualitative methodology combining thematic, dialogical and comparative techniques.ResultsLaughter reliably marked interactional hotspots where talk about dependency, mortality and ageist stereotypes became sensitive. It acted as an embodied enthymeme that exposed—and regulated—tension between personal narratives and dominant ageing imaginaries. Gender and class shaped these patterns: women’s humour negotiated autonomy within family relations, whereas men’s joking resisted the figure of the “useless old man”.DiscussionFraming laughter as an ideological symptom shows how affect and normativity are related in later-life discourse, extending critical-gerontology debates and providing a replicable toolset for multimodal data.